(3SDGd hLhGH aj GdWdGb GdKdGKs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3SFd TjN GdESdGe Hf JjejI GdMQGfi Yf QLd Wdb EeQCJg KdGKkG HcdeI hGMOI agd jbY Hg hGMOI Ce KdGK s
(3BNQgG (B:s
(3hbO HSWJ GdcdGe YdjgG ai ehGVY ai fMh eLdOjf hCcKQ hEfeG fHgfG YdjgG THjgkG dWjakG hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde hgh MSHfG hfYe Gdhcjd JeJ GdeSFdI hddg GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B11s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3bhHdJ hUMMJs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdMfHdjs